Genome-Wide Identification of Cassava Serine/Arginine-Rich Proteins: Insights into Alternative Splicing of Pre-mRNAs and Response to Abiotic Stress. (9th October 2019) - Gu, Jinbao; Ma, Siya; Zhang, Yuna; Wang, Dong; Cao, Shuqing; Wang, Zhen-Yu
Abstract: Serine/arginine-rich (SR) proteins have an essential role in the splicing of pre-messenger RNA (pre-mRNA) in eukaryote. Pre-mRNA with introns can be alternatively spliced to generate multiple transcripts, thereby increasing adaptation to the external stress conditions in planta. However, pre-mRNA of SR proteins can also be alternatively spliced in different plant tissues and in response to diverse stress treatments, indicating that SR proteins might be involved in regulating plant development and adaptation to environmental changes. We identified and named 18 SR proteins in cassava and systematically studied their splicing and transcriptional changes under tissue-specific and abiotic stress conditions. Fifteen out of 18 SR genes showed alternative splicing in the tissues. 45 transcripts were found from 18 SR genes under normal conditions, whereas 55 transcripts were identified, and 21 transcripts were alternate spliced in some SR genes under salt stress, suggesting that SR proteins might participate in the plant adaptation to salt stress. We then found that overexpression of MeSR34 in Arabidopsis enhanced the tolerance to salt stress through maintaining reactive oxygen species homeostasis and increasing the expression of calcineurin B-like proteins (CBL)–CBL-interacting protein kinases and osmotic stress-related genes. Therefore, our findings highlight the critical role of cassava SR proteins as regulators of RNA splicing and salt tolerance in planta.